Cross-layer resource allocation in wireless communications techniques and models from PHT and MAC layer interaction - Perez-Niera, Ana I.
As business modeling becomes mainstream, every year more and more companies and government agencies are creating models of their businesses. But creating good business models is not a simple endeavor. Business modeling requires new skills. Written by two business modeling experts, this book shows you how to make your business modeling efforts successful. It provides in-depth coverage of each of the four distinct business modeling disciplines, helping you master them all and understand how to effectively combine them. It also details best practices for working with subject matter experts. And i.